Analysis and assessment of the nutrients, biochemical indexes and heavy metals in the Three Gorges Reservoir, China, from 2008 to 2013. (1st April 2016) - Gao, Qiang; Li, Yi; Cheng, Qingyuan; Yu, Mingxia; Hu, Bo; Wang, Zhigang; Yu, Zhiqiang
Abstract: The Three Gorges Reservoir, the world's largest hydropower project, has operated stably for more than five years. To understand its water quality status, the nutrient and biochemical indexes, the total nitrogen (TN), the total phosphorus (TP), the potassium permanganate index (CODMn ), the five-day biochemical oxygen demand (BOD5 ) and fecal coliform (F. coli), as well as the heavy metals (Cu, Hg, As, Cd, Zn and Pb) of samples collected from 10 sites during the time period of 2008–2013 were studied via using multiple analysis approaches. For each parameter, pictures of the spatial and temporal distributions were presented, and the reasons behind their variation trends were elaborated. Principal component analysis (PCA) was applied to identify the types of pollution. The Canadian Council of Ministers of the Environment Water Quality Index (CCME-WQI) was calculated to concisely mark the water quality. In addition, a human health risk assessment of the heavy metals in a representative site was conducted. The results showed that the water quality state in the Three Gorges Reservoir was intricate but stable and acceptable from 2008 to 2013. The TN, TP and Pb were considered to be the key pollution indexes. Enforcements to alleviate industrial and urban pollution, along with ship management, have worked. The decrease in heavy metal concentrations from upstream to downstream was associated with the self-purification of the reservoir. However, rural pollution became worse in those years. Improper agricultural activity was an important reason for this trend. For local residents, drinking water was generally safe, but cancer caused by As and Pb is a potential issue. Graphical abstract: Highlights: An integrated analysis was conducted, including nutrient, biochemical and heavy metal. Spatial and temporal patterns of pollution were analyzed. Causes of water quality variations were elaborated. Types of pollution were identified and corresponding water quality indexes were presented. Carcinogenic potential of Pb and As should be concerned based on health risk assessment.